Flexural Performance of PVA Reinforced ECC Beams: Numerical and Parametric Studies - Hind, Mahmood Khudhur; Mustafa, Özakça; Abdolbaqi, Mohammed Khdher; Talha, Ekmekyapar (Universiti Malaysia Pahang, 2016)
Engineered cementitious composite (ECC) refers to the group of cementitious mixtures possessing the strainhardening and crack control abilities. In this research, the mechanical performance of ECC beams will be investigated with respect to the effect of aggregate size and amount, by employing nonlinear finite element method. The validity of the models were verified with the experimental results of the ECC beams under monotonic loading. Based on the numerical analysis method,nonlinear parametric study was then conducted to evaluate the influences of various parameters on the flexural stress and flexural deflection of ECC beams. A new models that accounts for the ECC aggregate content (AC), ECC compressive strength (fECC), and maximum aggregate size (Dmax) parameters are proposed. The analytical results obtained from the proposed models were compared with experimental results obtained from 57 ECC beam tests previously published. The simulation results indicated that when increase the aggregate size and content no definite trend in flexural strength is observed and the ductility of ECC is negatively influenced by the increase of aggregate size and content. Also, the ECC beams revealed enhancement in terms of flexural stress, strain, and midspan deflection when compared with the reference beam (microsilica MSC), where, the average improvement percentage of the specimens were 45%, 1242%, and 1427.15%,respectively. These results are quite similar to that of the experimental results, which provides that the finite element model is in accordance with the desirable flexural behaviour of the ECC beams. Furthermore, the proposed models can be used to predict the flexural behaviour of ECC beams with great accuracy.